Uncertainty analysis of linear vertical bending moment in model tests and numerical prediction. (1st October 2022) - Si, Hailong; Yang, Peng; Gu, Xuekang; Hu, Jiajun; Tian, Chao; Feng, Qiandong; Ni, Yang
Highlights: A set of wave load measurement accuracy and uncertainty analysis method for ship model in wave basin is established based on the uncertainty expansion theory. The significant factors affecting the accuracy of wave load test are assessed by the linear multi-segment model tests of wave loads. Two numerical methods are used to evaluate the prediction error and uncertainty of linear vertical moment, horizontal moment and torsional moment. Abstract: Due to the complexity of model tests of wave loads, some random factors affect the accuracy of measurement results, such as model processing, coefficient calibration, counterweight, and wave creation quality. Based on the uncertainty expansion theory, a set of wave load measurement accuracy and uncertainty analysis methods for ship model in wave basin were established. The significant factors affecting accuracies of wave load tests were assessed by the linear multi-segment model tests of wave loads. Two numerical methods were used to evaluated the prediction errors and uncertainties of the linear vertical moment, horizontal moment and torsional moment. The research shows that with the updating of test instruments and approaches, the standard uncertainty of model test decreased. The uncertainty caused by the calibration coefficient was the largest, followed by the moments of inertia of ship models. As the wave direction changes from head seas to oblique seas, the errors and uncertainties of numerical predictions begin to increase. The numerical predicting errors of vertical bending moments was the smallest, followed by horizontal bending moment and torsion error was the largest.